Comparison of effect of remimazolam and propofol on respiration of patients under deep sedation for colonoscopy: a prospective multicenter randomized controlled trial - Zhengjia Wang; Renshu Zhan; Liqun Mo; Jin Zhang; Jie Hu; Shoupeng Tan; Qiongzhen He; Ping Li; Wekong Sun; Xiaobin Wang; Jun Jiang; Li Liu; et al. (European Journal of Medical Research)
Abstract Background Remimazolam recently became available as a sedative. The comparison of the respiratory suppression effects of remimazolam and propofol under deep sedation for colonoscopy was not thoroughly unclear, particularly with regard to the novel metric of time to first airway intervention. The goal of this study was to systemically compare the respiration profiles of the patients sedated with remimazolam and propofol at the comparable sedation level in the patients undergoing colonoscopy. Methods Four hundred-fifty outpatients were randomly assigned to remimazolam (Group Rem, n = 225) and propofol (Group Pro, n = 225). The target sedation level was the modified Observer’s Assessment of Alertness/Sedation ≤ 2. The primary outcome was elapsed time from anesthesia induction to first airway intervention. Secondary outcomes included incidence and severity of hypoxia and apnea, minute ventilation (MV), tidal volume (TV), and respiratory rate (RR). Results The elapsed time from induction to the first airway intervention was 11 ± 8 min in Group Rem (n = 208) vs. 5 ± 6 min in Group Pro (n = 208, P < 0.001). Patients in Group Rem required less frequent airway intervention and had a lower incidence of and shorter duration of apnea than patients in Group Pro (all P < 0.001). MV at 1 min, 2 min, 4 min post-induction, and at the end of the procedure were higher in Group Rem than those in Group Pro (P < 0.001). Conclusions Patients sedated with remimazolam vs. propofol during colonoscopy maintain improved respiration and require less frequent airway intervention, and have lower incidence of adverse events. Clinical trial registration and registry URL ChiCTR2000034527, registered at www.chictr.org.cn